A rapid analysis method for determining current status of existing buildings:: A conceptual framework - Yildizlar, Baris; Akcay, Cemil; Öztorun, Namik Kemal (Revista de la Construcción. Journal of Construction, 2018)
Considering the loss of lives and economical loss arising out of earthquake motions, it becomes necessary to determine the safety levels and vulnerability of the existing buildings especially in the urbanized areas and to take due precautions. As a matter of fact, it is not convenient to determine the safety levels of a large number of structures by using the common analysis methods with respect to the temporal and economical aspects, because there are great numbers of structures, fewer expert engineers in proportion to number of structures, the said process is economically large-scaled, and it takes too long to determine the structural safety, as well as the fact that it is possible to determine the safety level of a structure by using many parameters. In order to determine the safety levels of structures, it is required to develop fast evaluation methods which are free from any subjective parameters and based on local specifications and compatible with production techniques and practices. In line with this purpose, it is necessary to carry out structural surveys to determine the safety levels of structures by using the parameters, which should be chosen in the minimum basis, but assuring the reliability criteria. The algorithm containing the minimum evaluation criteria, which are essential to evaluate the present condition of structures in accordance with the mathematical bases, and a quick evaluation method featuring the said algorithm are introduced in the presented study. The structural safety of many structures against earthquake effects has been determined fast and correctly by using the developed method.